Neyman-Pearson Hedging and Dynamic Measures of Risk - Michael Kohlmann (University of Konstanz, Center of Finance and Econometrics (CoFE), 2000)
In both complete and incomplete markets we consider the problem of fulfilling a financial obligation xc as well as possible at time T if the initial capital is not sufficient to hedge xc. This introduces a new risk into the market and our main aim is to minimize this shortfall risk by making use of results from bsde theory.
urn:nbn:de:bsz:352-opus-4941
Keywords: 330; Portfolio-Management; Hedging; Risiko; Analysis; Stochastischer Prozess; Kontrolltheorie; Black-Scholes-Modell; Theorie